LITERATUR REVIEW: PENGARUH PERUBAHAN SOSIAL TERHADAP PENDIDIKAN DI INDONESIA - Febri Kartika, Wilda; Sri Sumartiningsih; Agus yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the current era of education, teachers are faced with demands to optimize the potential, creativity, interests and talents of each student in various existing social changes. This research was conducted to provide better insight into how social change can affect education and vice versa. The method used in this research is the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) by analyzing articles through article identification, filtering, and inclusion. The articles used were articles published between 2014 and 2024 and 80 articles were found to be relevant. After conducting a thorough analysis, the researcher decided to examine 7 articles. The results obtained are that education plays an important role in shaping and directing social change. Education not only prepares individuals to adapt to social dynamics, but also maintains the preservation of existing cultural and social values. The impact of social change can be positive or negative. Adaptive education is able to direct social change towards progress and a better quality of life, while failure to adapt can lead to social decline.